PENGARUH MODEL PENGAJARAN TERINTEGRASI TERHADAP MOTIVASI BELAJAR MAHASISWA - Hapsari, Intan Putri (Sanata Dharma University, 2025)
This study examines the effect of an integrated teaching model that combines Flipped Classroom, Authentic Learning, and Ignatian Pedagogy. The study was conducted to observe the learning motivation of Biology Education students in Biosystematics, specifically addressing the topic of “The Role of Biosystematics in Research.” A mixed-methods approach with a Convergent Parallel design was implemented to obtain the quantitative and qualitative data. The quantitative data were collected through a learning motivation questionnaire using a 6-point Likert scale, and the qualitative data were gathered from open-ended questions to support the analysis of the quantitative data. The results show a high average motivation score from 5.37-5.40, with 82.86% to 97.14% of respondents choosing scores 5 and 6 for each item. These findings show that the integrated teaching model encourages engagement through intrinsic reflection and commitment to being morally responsible. Qualitative data reveal that students had been able to experience meaningful learning within real-world contexts, so they felt challenged to be morally responsible. In conclusion, the integrated model supports learning motivation by acting on character development through Ignatian Pedagogy as well as the 4C values (Competence, Conscience, Compassion, and Commitment).